Estimating Households' Benefits from Domestic Wastewater Treatment in Cagayan De Oro, Philippines: A Contingent Valuation Approach - Palanca-Tan, Rosalina (Archīum Ateneo, 2016)
This paper surveys the current water supply, sanitation and sewerage facilities available to households in Cagayan de Oro, and their awareness of and attitudes towards water and wastewater issues. Survey results reveal inadequate and sub-standard domestic wastewater treatment facilities both on the household and community levels as well as some degree of household indifference. Using contingent valuation method, this study estimates the value that households in Cagayan de Oro attach to the benefits that they can derive from a domestic wastewater treatment program. Mean willingness to pay for the planned program range from PhP3.29 (parametric estimate) to PhP6.01 (non-parametric) per m3 of water consumption, which falls short of the projected program cost of PhP7.11 per m3 of water. It may, therefore, be necessary to raise people's understanding of the externalities of their water consumption to make the planned domestic wastewater program viable. It may also be necessary to incorporate the sewerage and sanitation charge within the water rate schedule so as to ensure households' payment for the proposed wastewater treatment program for the city.